PENINGKATAN RESIKO PRESBIKUSIS PADA PASIEN LANSIA HIPERTRIGLISERIDEMIA DI RSI SITI RAHMAH - Elsa Ardana; Triansyah, Irwan; Nilas Warlem; Ade Teti Vani; Aryaldy Zulkarnaini; Revivo Rinda Pratama (Yayasan Nusantara Hasana Berdikari, 2024)
Background: Presbycusis is a sensorineural hearing disorder that causes loss of hearing ability in old age. Dyslipidemia is a risk factor for presbycusis, namely an imbalance in lipids such as cholesterol, LDL, triglycerides and HDL. Excessive triglyceride levels will increase the risk of atherosclerosis. The formation of atherosclerotic plaque will result in thickening of the blood vessel walls and narrowing of the lumen, resulting in obstruction of blood flow and reducing oxygen transport which can cause ischemia in the cochlea and disrupt hearing function. Objective: Determine the relationship between increased triglyceride levels and presbycusis in elderly patients with dyslipidemia at RSI Siti Rahmah. Method: This type of research is analytical observational research using a case control design and the type of data used is primary and secondary data using consecutive sampling techniques. Results: Presbycusis was most commonly found in the 60-69 year age group (58,33%), presbycusis was mostly found in dyslipidemia elderly with increased triglyceride levels (75.0%), and the highest grouping of triglyceride levels was found in the high group (41,67%). There is a significant relationship between triglyceride levels in elderly patients with dyslipidemia and the incidence of presbycusis (P-value 0.001) and the OR calculation shows that elderly people with dyslipidemia with increased triglyceride levels are 6 times more at risk of experiencing presbycusis compared to elderly people without dyslipidemia. Conclusion: There is a significant relationship between increasing triglyceride levels and presbycusis in elderly with dyslipidemia at RSI Siti Rahmah